DIAGNÓSTICO SITUACIONAL EM SAÚDE: PERFIL DE MORTE DA POPULAÇÃO RESIDENTE DO MUNICÍPIO DE BETIM - Pego, Aline Silva; Sousa, Gabriela Oliveira; Silva, Gisele Paloma da; Pereira, Iury Augusto Otoni; Santos, Karen Carvalho; Lima, Larissa Shirley Gomes; Felisberto, Juliana Mara (Sinapse Múltipla, 2020)